Perancangan Objek Wisata Bahari dan Konservasi Ikan Air Laut di Pantai Bandengan Jepara Dengan Penerapan Arsitektur Tropis - Aditya Bagus Nugroho; Karya Subagya; Sri Kurniasih (FAKULTAS TEKNIK UNIVERSITAS BUDI LUHUR, 2022)
Maritime tourism is one of Indonesia's attractions and the biggest driver of the economy. so that to move Indonesian tourism to be better, its development requires a multidisciplinary domain, one of which is the marine tourism sector, which in terms of potential, the availability of land and natural resources is very large. With the design of Marine Tourism Objects and Marine Fish Conservation, it is hoped that it can accommodate tourism management and the development of seawater fish, especially in the Bandengan area of ​​Jepara, Central Java. This tourist area applies the concept of tropical architecture that adapts to the climatic conditions of the Jepara region to support the function of the building and comfort for its users.